Diseño y construcción de los instrumentos de medición para un biorreactor prototipo - Rodríguez Arévalo, A. C.; Cabrera Llanos, A. I.; Valencia Flores, J. I. (Revista Mexicana de Ingenieria Biomedica, 2003)
The instrumentation of a bioreactor prototype is settled in the control of yeasts that allow us to optimize the process. The control strategy begins with the measurement of the variables that will provide an adequate environment in a fermentative process. The knowledge of the bioreactors, their requirements and specific operation, as well as the electronic circuits of the measurement devices, was required in order to design and construct all the necessary elements for the monitoring of the variables involved in a fermentative process. Not only the design of the devices for the measurement, but also the controllers for the variables such as agitation speed, temperature, water level and impedance was performed. Furthermore, a work station was constructed, based on the characteristics of functionality, dimensions and transport of the prototype. Finally, the control of a fermentative process in a prototype bioreactor with instruments of our own design and construction was achieved.